Theoretical and experimental short-term behavior of non-symmetrical wall pile retaining systems. (1st April 2016) - Gil-Martín, L.M.; Carbonell-Márquez, J.F.; Fernández-Ruíz, M.A.; Hernández-Montes, E.
Graphical abstract: Highlights: It focuses on a wall pile system proposed by the authors. The system is called asymmetrical reinforcement of wall piles. This system is studied for the first time under serviceability limit states. This system is for the first time used in a complete construction. Abstract: Optimized non-symmetrically reinforced piles for retaining walls constitute a new structural element recently used in constructions such as the underground floors of San Antoni Market in Barcelona or in the Riyadh metro. Piles usually have circular cross sections with longitudinal reinforcement composed of bars of the same diameter and with constant clear distances between them. The use of non-symmetrical piles in retaining walls means savings of up to 50% in the weight of the longitudinal reinforcement, compared with traditional symmetrical piles. Intuition suggests that a non-symmetrical pile, compared with its symmetrical counterpart -both having the same ultimate flexural moment-, deforms less and has smaller crack widths. This point is analyzed in this paper both theoretically and experimentally. The majority of the studies conducted on RC members were developed only for rectangular cross sections. In this paper, results from an experimental campaign of circular RC cross-sections are presented. The main objective of this campaign is the formulation of the effective area of concrete in the tension stiffening effect of RC circular cross-sections.